Systemic Arterial Hypertension in the Family Health Strategy: a literature review (Research, Society and Development, 2022)
Objective: To carry out a literature review on the approach to patients with Systemic Arterial Hypertension in the Family Health Strategy and the importance of counseling to strengthen the bond between care professionals and users. Method: This study was conducted from bibliographic searches in the SciELO database, to identify relevant articles, published between 2014 and 2019. Results: It was observed that the main factors that hinder better service include geographic and organizational barriers, including the lack of home visits, discontinuity of care, and bureaucracy. On the other hand, care always provided by the same professional, decentralization and adequate therapeutic communication can help in the continuity of care for patients with hypertension. Conclusion: It is necessary to strengthen the dialogue between health professionals and users for better monitoring and reception of patients with arterial hypertension.